SIFAT OPTIK NANOPARTIKEL PERAK (Ag-NPs) MENGGUNAKAN BIOREDUKTOR EKSTRAK KULIT SEMANGKA KUNING - Hazelina Adzani; Ari Sulistyo Rini (Universitas Riau, 2020)
Synthesis of silver nanoparticles was carried out by a reduction method using yellow watermelon rind extract. Variation of sample on this synthesis was doing with ratio volume extract and ag, i.e., 1:3 and 3:1. This synthesis has been successfully carried out using 1M NaOH as a stabilizer. The formation and stability of silver nanoparticles was observed through Uv-vis absorbance spectrum. The results of the analysis using Uv-Vis spectroscopy show the formation of silver nanoparticles at wavelengths of 440-446 nm with absorbance values of 0.8356 a.u and 1.0458 a.u respectively. The FTIR analysis showed the existence of a polyphenol group functional with a range of wave numbers 601.82-3359.18 cm-1. This result concludes that yellow watermelon rind extract is involved in reducing Ag+ to Ag0.